Public Awareness and Inclination to Do Cash Waqf in Indonesia - Amalia, Rahmi; Ali, Mohammad Mahbubi (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
The application of cash waqf in the general public has not developed widely compared to its considerable potential. This study aims to show how public awareness and inclination of the community in understanding the existence of cash waqf and trying to find normative reasons that become obstacles to the implementation of cash waqf. This study used quantitative methods and by descriptive approach to describe the results through an in-depth discussion. Respondents consisted of 390 people from various backgrounds spread across Indonesia, such as religion, age, education, income, and province. The findings indicate that, in general, the knowledge of the Indonesian people regarding cash waqf is still shallow in the classifications mentioned in this study, because many people still didn’t know well what waqf is. Moreover, most of the respondents stated that infaq is more convenient than waqf. However, this is driven by several obstacles that need to be considered when designing educational and outreach methods in the future. The role of this research is expected to lead to the fulfillment of the potential of cash waqf, which has such a significant function in society. This study could be used as a formulation of a socialization strategy to attract wakif candidates in Indonesia.